Verbal morphology in the Database of New Borrowings into Lithuanian - Pakerys, Jurgis (Taikomoji kalbotyra, 2014)
The Database of New Borrowings into Lithuanian lists 129 verbs which were either directly borrowed or derived from the borrowed nominal and adjectival stems. In terms of morphosyntactic adaptation, two suffixes, viz. uo ti and in ti, are used as indirect insertion strategy devices (Wohlgemuth 2009: 94 ff.). The suffix uo ti is the most productive verbalizer in modern Lithuanian and is predominantly used to integrate the so called internationalisms in the standard language, while in ti is the main factitive/causative affix and is employed in the non standard language domain to accommodate the verbal borrowings coming mostly from English. In very many cases, verbs, nouns and some adjectives sharing the same stem were borrowed and I argue that a synchronic derivational link between them can be recognized in Lithuanian, no matter what the derivational history of these words in the donor language was. If a borrowed verb has a suffix, but no corresponding noun or adjective is found in the current usage, the suffix can be interpreted as a device of morpho-syntactic adaptation only. Compared to uo ti and in ti, other suffixes are only rarely attested in the database, but they clearly reflect productive types of verb formation, namely, the denominal similatives in au ti and the deadjectival inchoatives in ė ti. The data on prefixal and reflexive derivatives is too scarce to note any definite trends. As far as inflectional productivity is concerned, in ti and uo ti definitely play a major role in enriching the classes characterized by the present stem affixes of the a-type and the past stems affixes of the o-type. The inflexion of verbs in uo ti is also affected by morpho-phonological alternation of the suffix to resolve hiatus, viz. the infinitive stem has /uo/ (no hiatus), the present stem is augmented by the palatal glide /j/ ( uoj ), while in the past stem, /uo/ is replaced by /av/ (i.e. uo ti, uoj a, av o).
Keywords: verbal borrowings; morphological adaptation; verbal derivation; verbal suffixes; standard language; non-standard language